Transcriptomic Analysis of Changes in Gene Expression During Flowering Induction in Sugarcane Under Controlled Photoperiodic Conditions - Manechini, João Ricardo Vieira; Santos, Paulo Henrique da Silva; Romanel, Elisson; Brito, Michael dos Santos; Scarpari, Maximiliano Salles; Jackson, Stephen; Pinto, Luciana Rossini; Vicentini, Renato (Frontiers in Plant Science, 2021)
Flowering is of utmost relevance for the agricultural productivity of the sugarcane bioeconomy, but data and knowledge of the genetic mechanisms underlying its photoperiodic induction are still scarce. An understanding of the molecular mechanisms that regulate the transition from vegetative to reproductive growth in sugarcane could provide better control of flowering for breeding. This study aimed to investigate the transcriptome of +1 mature leaves of a sugarcane cultivar subjected to florally inductive and non-inductive photoperiodic treatments to identify gene expression patterns and molecular regulatory modules. We identified 7,083 differentially expressed (DE) genes, of which 5,623 showed significant identity to other plant genes. Functional group analysis showed differential regulation of important metabolic pathways involved in plant development, such as plant hormones (i.e. cytokinin, gibberellin, and abscisic acid), light reactions, and photorespiration. Gene ontology enrichment analysis revealed evidence of up-regulated processes and functions related to the response to abiotic stress, photoprotection, photosynthesis, light harvesting, and pigment biosynthesis, whereas important categories related to growth and vegetative development of plants, such as plant organ morphogenesis, shoot system development, macromolecule metabolic process, and lignin biosynthesis were down-regulated. Also, out of 76 sugarcane transcripts considered putative orthologs to flowering genes from other plants (such as Arabidopsis thaliana, Oryza sativa, and Sorghum bicolor), 21 transcripts were DE. Nine differentially expressed genes related to flowering and response to photoperiod were analysed either at mature and spindle leaves at two development stages corresponding to the early stage of induction and inflorescence primordia formation. Finally, we report a set of flowering-induced long non-coding RNAs and describe their level of conservation to other crops, many of which showed expression patterns correlated against those in the functionally grouped gene network.